Ultrasonic system for avoiding car collision - Abdul Rahman, Mohd. Zamani (2013)
This research project is about design of avoiding car collision using ultrasonic transducer. The ultrasonic sensor has been choosing due to the huge advantages compare to the other available sensors in the market. The transmitted signal and received signal from the sensor have been evaluated and compared with the environmental noise to provide correct information for the avoiding collision system. A software system has been designed to analyze the signals and to develop a reliable signal processing algorithm for the avoiding collision system. The actual data have been compared with the data from the designed system. The results from this project demonstrate that the system could supply correct information and reduce the number of false information to driver.